Just Transition or Just Illusion? A Critical Assessment of Climate and Development Programmes in Madagascar - Hoby Nasandratra Andriamiandrisoa; Ramalina Ranaivo Mikea Manitra (Jurnal Ilmu Sosial dan Humaniora, 2025)
Climate change impacts in Madagascar have intensified concerns about the fairness of current adaptation and development programmes, making the notion of a just transition an urgent policy and research priority. This paper aims to examine the extent to which four justice dimensions of just transition are reflected in key climate initiatives, with a focus on identifying strengths and gaps. The study uses a qualitative systematic literature review combined with thematic analysis, following ROSES guidelines for data collection. Each justice dimension is assessed using specific criteria, focusing on community participation for procedural justice, benefit and burden allocation for distributive justice, compensation and livelihood recovery for restorative justice, and the recognition of cultural, gendered, and historically marginalised groups for recognition justice. Findings show that procedural justice is only partially realised, as community participation remains mostly operational rather than influential in decision making. Distributive justice appears uneven, with benefits concentrated in semi urban areas and persistent disparities affecting rural populations, women, and land dependent households. Restorative justice is limited, because compensation and long term livelihood recovery measures remain insufficient compared with the scale of environmental and socio economic harm. Recognition justice shows selective progress, especially in projects targeting drought affected and coastal communities, yet it does not adequately address deeper cultural, gendered, and historical forms of marginalisation. The paper concludes that Madagascar’s programmes demonstrate intent but fall short of delivering truly “just transition,” and it recommends institutionalising participatory mechanisms, designing equitable benefit sharing frameworks, expanding reparative policies, and adopting a national just transition framework to guide future interventions.